Reading "Black Mirror" : insights into technology and the post-media condition - Battin, Justin Michael; Battin, Justin Michael; Duarte, German A.; Duarte, German A.; Apperley, Thomas H.; Carniel Bugs, Ricardo; Dalmasso, Anna Caterina; Facchetti, Andrea; Fordyce, Robbie; Galati, Gabriela; Giraldo-Luque, Santiago; Macey, Joseph; et al. (Edition Medienwissenschaft, 2021)
Very few contemporary television programs provoke spirited responses quite like the dystopian series Black Mirror. This provocative program, infamous for its myriad apocalyptic portrayals of humankind's relationship with an array of electronic and digital technologies, has proven quite adept at offering insightful commentary on a number of issues facing contemporary society. This timely collection draws on innovative and interdisciplinary theoretical frameworks to provide unique perspectives about how confrontations with such issues should be considered and understood through the contemporary post-media condition that drives technology use.